Self-care behaviors in older adults suffering from knee osteoarthritis: Application of theory of planned behavior - Jormand, Hanieh; Mohammadi, Nasim; Khani Jeihooni, Ali; Afzali Harsini, Pooyan (Frontiers in Public Health, 2022)
Background: Osteoarthritis is one of the most important reasons causing disablement. Educational intervention for self-care behaviors of patients suffering from knee osteoarthritis is important because its effect on quality of patient life decreases the economic burden of disorder on society and family. This study aimed to investigate the effect of educational intervention based on the theory of planned behavior (TPB) on promoting self-care behaviors in elderlies suffering from knee osteoarthritis. Methods: This quasi-experimental study was performed on 200 elderlies suffering from knee osteoarthritis in the rheumatology clinics of Shiraz, Iran, in 2019. The subjects were divided into two groups (100 experimental and 100 control). Before and after four months, both experimental and control groups filled a questionnaire. After administering a pre-test to both groups, only the experimental group was trained based on the TPB constructs on self-care behaviors in elderlies suffering from knee osteoarthritis in 8 sessions by presenting educational films and images and power points and group discussions for solving problems. Results: The mean age of the experimental group is 67.25±3.64, and the mean age of the control group is 66.12±3.50. The average scores of attitudes, subjective norms, perceived behavioral control, intention, and behavior before the educational intervention do not have significant differences in experimental and control groups, however, four months after the educational intervention, the paired t-test indicated significant enhancement in every construct in the experimental group, but control group has no significant changes. Conclusion: According to the results, the educational intervention has increased the self-care behaviors of patients suffering from knee osteoarthritis based on the theory of planned behavior. Therefore, the results of this study can be used in the theory-based intervention strategies for self-care behaviors of patients suffering from knee osteoarthritis.